Assessing and Achieving Quality in Qualitative Research: Clues for Researchers in Training - de la Cuesta Benjumea, Carmen (Investigación y Educación en Enfermería, 2024)
This article deals with the particularities of the quality of qualitative research, under the double lens of valuing it and ensuring it. While achieving the quality of qualitative research concerns only those who have opted for this methodology, assessing it is everyone’s business because researchers in training will encounter, in the literature reviews, qualitative studies on which they must reflect and estimate their quality. Appreciating the quality of a research work is a complex activity as it is situated within a context and conducted by individuals who use any of the means available to do so. The means they use are criteria as evaluation guides and criteria checklists. For researchers in training, I suggest some guiding criteria to evaluate qualitative publications and ensure quality during the research process, key issues that they must address.